Hubungan Dukungan Sosial Dengan Kualitas Hidup ODHA Pada Kelompok Dukungan Sebaya Solo Plus Di Surakarta - Rozi, Rahdatu Fakanur; , Ari f Widodo, A.Ke p., M.Kes; , Vi nami Yulian, S.Kep., Ns. Msc (2016)
HIV / AIDS is a problem that must be addressed not only by people with HIV/AIDS but also by all persons or communities associated with them. The main problem experienced by people with HIV / AIDS is a decreased immune systems that affect the onset of disease and decreased their quality of life. In addition to the physical, public acceptance of the existence of people with HIV / AIDS is a related factor to their quality of life sosially. Public support for people with HIV / AIDS is indispensable to improve the quality of life. This study aimed to analyze the correlation between social support on quality of life people with HIV / AIDS in Solo Plus Peer Group Support Surakarta. This research is descriptive correlative. The samples are 60 people with HIV / AIDS with the determination of purposive sampling techniques. The collection of data obtained from questionnaires. Data analysis was performed using univariate and bivariate analysis. The study concluded (1) social support to people with HIV / AIDS in Solo Plus Peer Group Support at Surakarta is moderately support, (2) quality of life people with HIV / AIDS in Solo Plus Peer Group Support at Surakarta is moderately, and (3) there is a positif correlation between social support and quality of life people with HIV / AIDS in Solo Plus Peer Group Support at Surakarta (p-value = 0.018) more and better social support, the quality of life people with HIV / AIDS is increasing.